2014
DOI: 10.14411/eje.2014.060
|View full text |Cite
|
Sign up to set email alerts
|

Generalist-specialist continuum and life history traits of Central European butterflies (Lepidoptera) - are we missing a part of the picture?

Abstract: Abstract. Analyzing life history traits of butterfly communities and faunas frequently reveals a generalist-specialist continuum as the main gradient, where species using wide arrays of resources, with good dispersal ability and fast development are distinguished from those using specialised resources, having limited dispersal ability and developing slowly. To ascertain the validity of the generalistspecialist approach for an intermediately species-rich Central European fauna, we analyzed ten life history trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 65 publications
1
51
0
Order By: Relevance
“…Similarly, Mattila et al (2006Mattila et al ( , 2008Mattila et al ( , 2011 demonstrated that diet and habitat specificity, overwintering in larval and pupal stages and short flight period and body size predispose Lepidoptera in Finland to distribution decline. Other studies highlighted the role of hostplant growth form and life strategies in relation to butterfly development, voltinism and larval specificity (Dennis et al 2004;Cizek et al 2006Cizek et al , 2012Bartonova et al 2014). We propose that the abovementioned life-history trait component offers a suitable substitute to the widely used, but confusing specialist-generalist continuum (e.g.…”
Section: Biological Dimensions Of Butterfly Vulnerabilitymentioning
confidence: 91%
See 2 more Smart Citations
“…Similarly, Mattila et al (2006Mattila et al ( , 2008Mattila et al ( , 2011 demonstrated that diet and habitat specificity, overwintering in larval and pupal stages and short flight period and body size predispose Lepidoptera in Finland to distribution decline. Other studies highlighted the role of hostplant growth form and life strategies in relation to butterfly development, voltinism and larval specificity (Dennis et al 2004;Cizek et al 2006Cizek et al , 2012Bartonova et al 2014). We propose that the abovementioned life-history trait component offers a suitable substitute to the widely used, but confusing specialist-generalist continuum (e.g.…”
Section: Biological Dimensions Of Butterfly Vulnerabilitymentioning
confidence: 91%
“…Therefore, we chose to adhere to the results without phylogenetic correction in order to cover the full set of documented species. Other studies also indicate that it is not always necessary to apply phylogenetic corrections in trait analyses (Mattila et al 2006(Mattila et al , 2011Päivinen et al 2005;Pavoine et al 2014;Bartonova et al 2014;Leingärtner et al 2014;De Bello et al 2015). This appears especially true for both this and the abovementioned studies that (partly) involve ecologically based traits, such as our climatic niche traits, which are less likely to be evolutionary conserved than morphological traits, such as body size.…”
Section: Phylogenetic Componentmentioning
confidence: 99%
See 1 more Smart Citation
“…Many, on closer investigation, prove to occur as metapopulations rather than single population units. These patterns were explored for European butterfl ies (Bartonova et al 2014 ) to reveal that the continuum was a rather poor predictor of conservation status. Species of high conservation value occurred among both specialists and mid-continuum generalists.…”
Section: Urban Insect Conservationmentioning
confidence: 99%
“…Such a situation leads Studies conducted to date have identiied a wide range of butterly characteristics that can potentially act as proxies for extinction risk. One of the most commonly addressed aspects in this respect is the division into generalists and specialists (Nylin and Bergström 2009;Ali and Agrawal 2012;Bartoňová et al 2014). The latter group includes a disproportionally high number of threatened species due to their stricter habitat and host plant requirements (Hodgson 1993;Purvis et al 2000;Fontaine et al 2007).…”
Section: Introductionmentioning
confidence: 99%